A Core Circuit Module for Cost/Benefit Decision - Hirayama, Keiko; Catanho, Marianne; Brown, Jeffrey; Gillette, Rhanor (Frontiers in Neuroscience, 2012)
A simple circuit for cost-benefit decision derived from behavioral and neural studies of the predatory sea-slug Pleurobranchaea may closely resemble that upon which the more complex valuation and decision processes of the social vertebrates are built. The neuronal natures of the pathways in the connectionist model comprise classic central pattern generators, bipolar switch mechanisms, and neuromodulatory state regulation. Marked potential exists for exploring more complex neuroeconomic behavior by appending appropriate circuitry in simulo.